Hyper Secure Algorithm for Text - Melad saeed (Al-Rafidain Journal of Computer Sciences and Mathematics)
Classical encryption methods depend on two basic encryption method, namely MONO ALPHABET and POLY ALPHABET. In this research, we developed a hybrid encryption algorithm to overcome the weaknesses in both methods and  employed  the basic methods  of themselves. The output  ciphertext is characterized  with the high security  when it does not give the expected results using the basics to break the code, namely, (adoptig the frequencies of the language used i.e. Frequency Analysis, besides Coincidence and Kasiski test). The problem of  distributing the secret key has been also overcome by adopting a new technique to  hide the  key inside the encrypted text in a nearly proposed way. Experimental result has been demonstrated that it is difficult to determine  the used encryption method ,in this algorithm we used MATLAB.